Double periodic composite right/left handed transmission line based leaky wave antenna by singular perturbation method - Mujumdar, Manisha D. (2014)
The paper proposes a Composite Right/Left Handed double periodic transmission line structure with both inductance and capacitance loaded. The structure exhibits leaky wave radiation and hence can be considered for leaky wave antenna (LWA) applications. We have theoretically obtained dispersion characteristics using Singular perturbation method. Also, the radiation e±ciency has been obtained for di®erent modulation indices. A novel leaky wave radiation has been obtained below the left handed passband with narrow bandwidth. The proposed structure has been fabricated on FR4 substrate and measured. The simulated and measured results seem to be in good agreement.